Handbook of research on nano-strategies for combatting antimicrobial resistance and cancer - Saravanan, Muthupandian, 1977-; Gopinath, Venkatraman, 1987-; Deekonda, Karthik, 1987- (IGI Global, 2020)
"This book examines (1) how to overcome the existing, traditional approaches to combat antimicrobial resistance and cancer; (2) how to apply multiple mechanisms to target the cancer cells and microbes; and (3) how the nanomaterials can be used as carriers"--